260 Starting a conversation: A community engagement beginning - Bashar Shihabuddin (Journal of Clinical and Translational Science)
Objectives/Goals: Community engagement in pediatric emergency medicine research is completed mostly when an exemption from informed consent (EFIC) is involved. A campaign was designed to engage the community surrounding an academic pediatric emergency department in an informal discussion on any pediatric acute care and research topics they felt were important. Methods/Study Population: A flyer inviting members of the community to a virtual session was circulated through social media and word of mouth. Five members of the community attended the first session, including one with healthcare expertise and another with clinical research experience. The participants were not asked any personal characteristic questions and were allowed to self-identify during the discussion, to maintain the informal nature of the session. Results/Anticipated Results: All the participants identified as women, and mothers to children ranging in age from 11 weeks to 14 years. The participants highlighted community engagement as pivotal for advancing children’s health. They stressed the inclusion of groups traditionally underrepresented in healthcare systems, including patients and families who rarely utilize acute services and whose children have no chronic medical conditions. Critical issues in emergency and urgent care for children were extensively discussed, with a focus on when acute medical treatment is necessary and determining appropriate healthcare settings – emergency departments, urgent care centers, or primary care offices. The participants unanimously supported research leading to practical solutions for improving children’s health outcomes. Discussion/Significance of Impact: A group of community caregivers can lead to an established collaborative effort to enhance children’s healthcare outcomes through community engagement, informed decision-making, and practical application of research findings to families and caregivers. A standing community meeting is planned based on the feedback from the first session.